Yolnuwu Monuk Gapu Wanga Sea Country Plan aYolnu vision and plan for Sea Country Management in North-east Arnhem Land, Northern Territory. (N.T. : Dhimurru Land Management Aboriginal Corporation, 2006)
Annotation pending.
Understanding Yolnu sea country -- Our concerns -- Invitations to stakeholders -- Moving forward -- Pronunciation of Yolnu words -- Notes.
Government agencies regarded as particularly important in the surveillance of sea country are: NT Fisheries, NT Police, Australian Quarantine and Inspection Services, Australian Customs, and the Australian Fisheries Management Authority (AFMA).
Non-government organisations include: WWF Australia, The Australian Conservation Foundation (ACF), The Wilderness Society, The Environment Centre of the Northern Territory, The Marine and Coastal Community Network, The Australian Marine Conservation Society, and The Humane Society International.
The Yolnu Community Councils and Associations include: Yirrkala Dhanbul and Marnarr Councils; the Rirratjinu and Gumatj Associations; and the Laynhapuy Association.
Title from document (viewed 1/4/09)
Text, images, pdf.
System requirements: reader required to view pdf document
Keywords: Australia. -- Department of Environment and Heritage; Alcan Gove Pty Ltd; Dhimurru Land Management Aboriginal Corporation; Environment Protection Authority; Laynhapuy Homeland Resource Centre; Manbuyna ga Rulyapa Indigenous Marine Protection Strategy; North Australian Indigenous Land and Sea Management Alliance; Northern Land Council (Australia); Northern Territory. Aboriginal Areas Protection Authority; Northern Territory. -- Department of Natural Resources, Environment, and the Arts; Northern Territory. -- Office of Indigenous Policy; Northern Territory; Parks and Wildlife Service of the Northern Territory; Yirrkala Community Education Centre; Yolnuwu Monuk Gapu Wanga Sea Country Plan; Coastal zone management -- Australia; Communication -- Political aspects; Cultural awareness -- Australia; Environmental protection -- Northern Territory -- Arnhem Land, Northeastern; Fisheries -- Australia; Intercultural communication -- Northern Territory -- Arnhem Land; Marine resources conservation -- Australia, Northern; Marine resources development -- Northern Territory -- Arnhem Land -- Planning; Negotiation -- Australia; Partnership -- Australia; Cultural heritage - Protection; Culture - Relationship to land; Culture - Relationship to place; Education; Enterprises - Tourism; Environment - Biodiversity - Animals; Environment - Conservation - Ecologically sustainable development; Environment - Land management; Environment - Sea management; Indigenous knowledge; Land rights - Hunting, gathering and fishing rights; Land rights - Sea rights; Mining industry - Bauxite / Aluminium; Research; Stories and motifs - Ancestor spirits; Stories and motifs - Creation / Cosmology; Yolngu languages (NT SD53); Yolngu people (NT SD53); Arnhem Land (NT); Lamamirri clan